2010
DOI: 10.1002/ajmg.b.31059
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of serotonin transporter, tryptophan hydroxylase 1 and 2 gene expression in the ventral prefrontal cortex of suicide victims

Abstract: Serotonergic signaling abnormalities have been implicated in suicide. Tryptophan hydroxylase (TPH), the rate limiting enzyme of serotonin biosynthesis and the serotonin transporter (SLC6A4), involved in the reuptake of serotonin from the synaptic gap, play major role in serotonergic signaling. In this study, we aimed to compare the levels of expression of these serotonin-related genes between suicide completers and controls and to identify genetic loci involved in their regulation. SLC6A4, TPH1, and TPH2 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 43 publications
(61 reference statements)
4
27
0
Order By: Relevance
“…This finding is in line with a recent report that measured TPH2 mRNA levels in the ventral prefrontal cortex (VPFC) of 39 suicide completers and forty matched controls, showing increased TPH2 expression levels in suicide victims (Perroud et al, 2010). Another study demonstrated no difference in the postmortem brain gene expression of TPH2 between the suicide group and the non-suicide group (De Luca et al, 2006a).…”
Section: Tryptophan Hydroxylasesupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in line with a recent report that measured TPH2 mRNA levels in the ventral prefrontal cortex (VPFC) of 39 suicide completers and forty matched controls, showing increased TPH2 expression levels in suicide victims (Perroud et al, 2010). Another study demonstrated no difference in the postmortem brain gene expression of TPH2 between the suicide group and the non-suicide group (De Luca et al, 2006a).…”
Section: Tryptophan Hydroxylasesupporting
confidence: 91%
“…Zill et al (2009) found no difference in TPH1 mRNA levels in the cortex of suicide victims compared with the controls. Similarly, Perroud et al (2010) found no difference in the postmortem brain gene expression of TPH1 in VPFC between the suicide group and the non-suicide group.…”
Section: Tryptophan Hydroxylasementioning
confidence: 86%
“…TPH2 is found in all serotonergic somata and proximal axons (Donner ff Handa 2009;Hale, Shekhar, and Lowry, 2011;Walther, 2003) and its levels are highly correlated with the amount of serotonin that the cells produce and their rate of activity (Calcagno et al, 2007;Cervo et al, 2005;Gutknecht et al, 2012;Patel et al 2004;Zhang et al, 2004). TPH2 mRNA and protein also exist in the cytoplasm of serotonergic terminals, including the prefrontal cortex (Carkaci-Salli et al, 2011;Sakowski et al, 2006;Perroud et al, 2010;Zill et al, 2007). This distal expression in the rat brain overlaps with serotonin immunoreactivity (Cohen et al, 1995;Weissmann et al, 1987), correlates with the local extracellular serotonin release (Calcagno et al, 2007;Chen and Miller, 2012), and for many years has also been suggested to indicate the capacity for local serotonin synthesis (Pickel, 1976;Weissmann et al, 1987;Perroud et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TPH2 mRNA and protein also exist in the cytoplasm of serotonergic terminals, including the prefrontal cortex (Carkaci-Salli et al, 2011;Sakowski et al, 2006;Perroud et al, 2010;Zill et al, 2007). This distal expression in the rat brain overlaps with serotonin immunoreactivity (Cohen et al, 1995;Weissmann et al, 1987), correlates with the local extracellular serotonin release (Calcagno et al, 2007;Chen and Miller, 2012), and for many years has also been suggested to indicate the capacity for local serotonin synthesis (Pickel, 1976;Weissmann et al, 1987;Perroud et al, 2010). Central serotonin systems are tremendously sensitive to developmental events in male rodents (reviewed in: Albert, VahidAnsari, and Luckhart, 2014), are implicated in the display of maternal behaviors in female rats (Barofsky et al, 1983;Pawluski et al, 2012;Zhao and Li, 2010), and when released in the mPFC is associated with anxiety-related behaviors (see Albert, Vahid-Ansari, and Luckhart, ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In an association analysis of 154 suicide completers and 289 control subjects, Perroud et al found tryptophan hydroxylase-2 gene expression levels to be increased in ventral prefrontal cortex of suicide victims. [45] …”
Section: Biological Factorsmentioning
confidence: 99%